ChemInform Abstract: Hydrocyanation of Arylidenemalonates Using Potassium Hexacyanoferrate(II) as an Eco‐Friendly Cyanide Source. Issue 24 (2nd June 2014) - Li, Zheng; Zhang, Yupeng; Wen, Fei; Yin, Junjun; Zheng, Huanhuan; Li, Hongbo; Yang, Jingya
Abstract The presence of two ester groups in the substrates is crucial as ethyl cinnamate (Ib) does not undergo hydrocyanation under the reaction conditions.